Immigrant family socialization: Perspectives from adult children of Mexican origin and their parents (Journal of Comparative Social Work, 2020)
Using convenient and purposive sampling augmented with snowball sampling, this study examines the perceptions of family socialization between two cultures, using in-depth interviews of 15 pairs of adult child-parent dyads (n=30) of Mexican origin in the United States. In sum, despite variations in the pace of acculturation, our study shows that both adult children and their parents proactively adopted compromising strategies (e.g. mutual respect, acceptance, openness, and realistic expectations) to bridge the differences in acculturation and reach common ground in family communication. Several core values and family practices, such as respect to family authority, family interdependence, retention/preservation of cultural heritage (e.g. language, customs, and identity), a strong work ethic, patriarchal gender norms, Mexican versus American parenting styles, and adult children striving for more freedom from traditional customs (e.g. conventional gender roles and living arrangements), were emphasized in Mexican immigrant family socialization in our study. Despite their differences in belief systems and ideologies, our study shows that family communication between the adult child-parent dyads was built on a set of implicit expectations that focus on minimizing family conflicts, yet providing a ‘culturally instrumental’ and supportive/caring context. In contrast to the postulation of the acculturation gap-distress model, our study found that discrepancies in acculturation between immigrant parents and their children were not necessarily associated with poorer family functioning and adjustment.